Rent sharing as a driver of the glass ceiling effect - Alessia Matano; Paolo Naticchioni (Institute for the Study of Labor (IZA), 2012)
In this paper we show that rent sharing plays a role in explaining the glass ceiling effect. We make use of a unique employer-employee panel database for Italy from 1996 to 2003, which allows controlling for observed individual and firm heterogeneity and for collective bargaining. Moreover, by means of IV quantile fixed effects estimates we can cope with unobserved heterogeneity and endogeneity. A discussion of different explanations is provided.
Keywords: C33; J16; J31; J41; L25; 330; rent sharing; gender wage gap; glass ceiling; quantile regressions; Lohndifferenzierung; Geschlechterdiskriminierung; Rent Seeking; Schätzung; Italien